A review of side underride statistics and protection device literature and designs. (1st January 2013) - Galipeau-Bélair, Patrick; El-Gindy, Moustafa; Ghantae, Srikanth; Critchley, David; Ramachandra, Sarathy
The goal of this paper is to provide a comprehensive review of the literature published on side underride protection devices (SUPDs). The overview examines current statistics and regulations concerning side underrides and tested designs and configurations, along with the aerodynamic advantage of trailer fairings which can be incorporated within the guards. Calculation methods to determine the severity of crashes on the occupants are also outlined and briefly discussed as to how they can be implemented for side underride crashes.